Comparing turbulence in a Kelvin–Helmholtz instability region across the terrestrial magnetopause. Issue 4 (5th February 2021) - Quijia, Paulina; Fraternale, Federico; Stawarz, Julia E; Vásconez, Christian L; Perri, Silvia; Marino, Raffaele; Yordanova, Emiliya; Sorriso-Valvo, Luca
ABSTRACT: The properties of turbulence observed within the plasma originating from the magnetosheath and the magnetospheric boundary layer, which have been entrained within vortices driven by the Kelvin–Helmholtz Instability (KHI), are compared. The goal of such a study is to determine similarities and differences between the two different regions. In particular, we study spectra, intermittency and the third-order moment scaling, as well as the distribution of a local energy transfer rate proxy. The analysis is performed using the Magnetospheric Multiscale data from a single satellite that crosses longitudinally the KHI. Two sets of regions, one set containing predominantly magnetosheath plasma and the other containing predominantly magnetospheric plasma, are analysed separately, thus allowing us to explore turbulence properties in two portions of very different plasma samples. Results show that the dynamics in the two regions is different, with the boundary layer plasma presenting a shallower spectra and larger energy transfer rate, indicating an early stage of turbulence. In both regions, the effect of the KHI is evidenced.